Show that the point (3, 7) lies on the line y = 2x + 1

Answers

Answer 1
Answer: Just plug in the point
x = 3 and y = 7
Y = 2(3) + 1
Y = 6 + 1
Y = 7
That’s how to prove it

Related Questions

ABCD is a rectangle with angle abd=40 determine angle dbc
Correct answers only please!What is the check digit (d) for the UPC bar code shown below?A. 2B. 4C. 6D. 8
4’ square?* peterminter
Solve for X4X-(9-3X)=8X-1
ANYONE CAN HELP ME WITH THESE QUESTIONS PLEASE ASAP

Convert 0.14 kilograms to grams

Answers

Hey there, 0.14 kilograms is 140 grams, All I did was 0.14*1000 and that gave me 140
the answer would be 140 grams because there are 1000 grams in a kilogram. when you change from a greater unit to a smaller one, you multiply. 0.14 multiplied by 1000 is 140

PLZ HELP IS DUE TODAYYY!! ‼️‼️ (there’s a pic of the problem)

Answers

Answer: x--1

Step-by-step explanation:

When you look at the tables the only x that is the same and gives the same answer is -1.

Angles geometry help me out please

Answers

Answer:

Angle name for 1&2 is Adjacent

What are the first three terms of the sequence represented by the recursive formula an=n^2-an-1 if a5=14 1/4

Answers

Answer:

B. 0.25, 3.75, 5.25

just convert what the person above said but into decimals

Answer:

  1/4, 3 3/4, 5 1/4

Step-by-step explanation:

Solving for a[n-1], we get ...

  a[n-1] = n^2 -a[n]

Then ...

  a[4] = 5^2 -a[5] = 25 -14 1/4 = 10 3/4

  a[3] = 4^2 -a[4] = 16 -10 3/4 = 5 1/4

  a[2] = 3^2 -a[3] = 9 -5 1/4 = 3 3/4

  a[1] = 2^2 -a[2] = 4 -3 3/4 = 1/4

Then the first three terms are a[1], a[2], and a[3]:

  1/4, 3 3/4, 5 1/4

Michael is 4 times as old as Brandon and is also 27 years older than Brandon. Please answer CORRECTLY !!!! Will mark brainliest !!!!!!

Answers

Answer:

108

Step-by-step explanation:

Mike's current age, be M

Then Brandon's is: M - 27

Also, M = 4(M - 27)

M = 4M - 108

M - 4M = - 108

- 3M = - 108

Which expression is equivalent to n2 + 26n + 88 for all values of n?(n + 8)(n + 11)

(n + 4)(n + 22)

(n + 4)(n + 24)

(n + 8)(n + 18)

Answers

Answer:

Option B is correct.

The expression which is equivalent to  n^2+26n+88  is; (n+22)(n+4)

Explanation:

Given the equation: n^2+26n+88 for all values of n.

The quadratic equation in this form; ax^2+bx+c =0

First find two numbers that multiply to give ac and add to give b.

From the given equation;

a =1 , b = 26 and c =88

then,

the two number that multiply to give ac =88 is, 22 or 4

and they add up to give b=26 (i.e 22+4)

Now, rewrite the middle term i.e 26n with 22n and 4n , we have

n^2+22n+4n+88=0

Now, factor the first two terms and last two terms,

n(n+22)+4(n+22)

we see that (n+22) is common to both terms so, we have;

(n+22)(n+4)

Therefore, the expression (n+22)(n+4) is equivalent to  n^2+26n+88

Check:

(n+4)(n+22) = n\cdot n+ 22n+4n+88=n^2+26n+88   [ True]



Solutions 

The expression equivalent to n^2 + 26n + 88  is 

n^2 + 26n + 88
(n + 4)(n + 22)